Quantum measurement : beyond paradox - Healey, Richard; Hellman, Geoffrey (Minnesota studies in the philosophy of science ;, 1998)
With relativity theory, quantum mechanics stands as the conceptual foundation of modern physics. Editors Richard A. Healey and Geoffrey Hellman marshal the resources of leading physicists and philosophers of science, skillfully joining their insights and ingenuity to yield some of the most innovative and altogether promising thought to date on this enigmatic issue.